EATING DISORDERS IN WOMEN AND PSYCHOLOGICAL FACTORS - Rizvance Masan, Sehida; Çobanoğlu, Gizem (International Scientific Journal Vision, 2024)
Eating disorders are disorders that affect people's mental and physical development. Conditions such as the environment and the physiological structure of the individual affect the individual. Generally, it can be seen in individuals of all ages, regardless of whether they are male or female. The reason it is common, especially in women, has been explained as women's self and aesthetic concerns. The individual's anxiety about being overweight, not wanting to be fat, maturing early, and wanting to be physically liked cause changes in the nutritional level and shape. On the other hand, familial factors also cause eating disorders. These are why the individual's family is overprotective and dominant, there are obese individuals in the family, and the individual has conflicts with his family. Nutritional changes made by the individual in the social process to make himself accepted or unhealthy diet and heavy exercise also cause eating disorders. In the individual's environment, efforts to comply with the perceptions of beauty imposed by society, the effect of the media in this process, and the anxiety of conforming to the standards of physical attractiveness trigger this situation. A woman with social anxiety changes her diet. Heavy diets, additional medications, heavy exercises, and behaviors that disrupt the eating pattern (such as vomiting) lead to serious illnesses. The process that starts with bodily aesthetic anxiety causes problems that will lead to situations that threaten the individual's life. In this process, the individual experiences physical and mental discomfort. Individual, familial, and social factors and eating disorders affect the physical and mental health of the individual. There are many eating disorders within the experienced process, effects, and results. These; include pica, anorexia nervosa, bulimia, binge eating disorder, emotional eating disorder, and an unclassifiable eating disorder.